Fabrication and characterisation of low temperature bonding via copper nanowire arrays - Nadia Eddy Razali (2011)
This research involves the electrical and mechanical characterization of thermocompressionally bonded copper nanowires. Copper nanowires were fabricated via electrodeposition into anodic alumina oxide (AAO) templates. Electrodeposited samples were then diced into 1 mm by 1 mm chips before thermocompressionally bonded to an electrical test structure in a low vacuum furnace for 1 hour. Blanket copper film to film (F-F) samples were also bonded to the electrical test structures under the same bonding conditions. Copper nanowire samples (NW-F) were bonded to the electrical test structure at 200 °C and 300 °C, while F-F samples were bonded at 200 °C, 250 °C and 300 °C. Electrical characterization was done by four-point probe, while mechanical characterization was achieved by shear test. It was observed that blanket F-F samples exhibit an ohmic contact. On the other hand, NW-F samples resembled a Schottky contact. The resistance for samples bonded at 300 °C was generally higher than that of 200 °C and had a larger standard deviation for both F-F samples and NW-F samples. Shear strength results show that the bond strength for NW-F samples was higher than F-F samples at 200 °C. However, at 300 °C, the F-F samples had a higher shear strength than the NW-F samples. In both NW-F samples and F-F samples, the effect of the presence of oxides in the bond interface was extensive. Annealing in N2 and forming gas were carried out, but improvements on the electrical and mechanical properties were not significant.